Annals of Library and Information Studies: A Bibliometric Analysis of the Journal and a Comparison with the Top Library and Information Studies Journals in Asia and Worldwide (2011–2017) - Segado-Boj, Francisco; Prieto-Gutiérrez, Juan José (Serials Librarian, 2020)
This article presents a thorough bibliometric analysis of research published in Annals of Library and Information Studies (ALIS), an India-based journal, for the period 2011–2017. Specifically, it compares this journal’s trends with those of other library and information science (LIS) journals from the same geographical area (India, and Asia as a whole) and with the 10 highest-rated LIS journals worldwide. The source of the data used was the multidisciplinary database Scopus. To perform this comparison, ALIS’ production was analyzed in order to identify authorship patterns; for example, authors’ countries of residence, co-authorship trends, and collaboration networks. Research topics were identified through keyword analysis, while performance was measured by examining the number of citations articles received. This study provides substantial information. The research lines detected through examining the keywords in ALIS articles were determined to be similar to those for the top LIS journals in both Asia and worldwide. Specifically, ALIS authors are focusing on metrics, bibliometrics, and social networking, which follows global trends. Notably, however, collaboration among Asia-based journals was found to be lower than that in the top-indexed journals in the LIS field, showing lesser internationalization. The results obtained present a roadmap for expanding the research in this field. © 2019, Published with license by Taylor & Francis Group, LLC
Keywords: bibliometrics; library and information science; literature review; network analysis; research trends; Scopus